THE SIGNIFICANCE OF THE SCIENTIFIC HERITAGE OF THE ANCESTORS IN RAISING THE SPIRITUAL IMAGE OF THE YOUTH (American Journal of Research in Humanities and Social Sciences, 2024)
It is known that it is marking a special period in the life of mankind. Whether it's world politics or the economy, sometimes people are shocked by changes. Integration processes that started with good intentions are increasing the risk of the unexpected. These threats do not choose a nation, a level of development, or a climate. It has become today's most important task to warn the youth of Uzbekistan about the danger that is spreading everywhere and knows no borders, and first of all, to educate them in the spirit of loyalty to the history of the Motherland, the heritage and values of their ancestors. Since the future of the state and the country is in the hands of young people, it is an extremely urgent and important task to set the right directions in education and training for them. As President Sh. Mirziyoev noted, "...first of all, the most important task is to form and educate the thinking of young people on the basis of enlightenment [1]". Of course, since we are mobilizing all our strength and opportunities for the happy living of our youth, the issue of spiritual education in this regard, without a doubt, is of incomparable importance [2].